Environment and pharmaceutical products case study: Biocatalysis of L-DOPA: Okolje in farmacevtski izdelki Prikaz primera: biokataliza L-DOPA - Findrik, Zvjezdana; Vasić-Rački, Đurđa (Acta Medico-Biotechnica, 2021)
Pharmaceuticals cure and treat diseases, and represent the benefit of modern society. However, their lifetime is much longer than many of us are aware. They are not fully absorbed or degraded in the body and their residues are the problem when they enter the sewage treatment systems. Drugs and their residues, in extremely low concentrations, can be detected in the environment: soil and water due to advances in analytical chemistry. Though their concentrations are low, they are a threat to the living organisms. Most of their long-term effects on living cells are unknown but many are known as negative. Not all pharmaceuticals are used; many drugs disappear and end up in the regular domestic waste, which is also a problem, because they present a hazardous waste, and should be treated as such. Dangerous waste is also emerging during the production of pharmaceuticals. Therefore, the clean chemical synthesis is one of the world’s priorities at this time. Among the methods, achieving this goal is the use of enzymes and whole cells as catalysts in chemical processes. So, if you look at the entire process of production of drugs and their consumption it can be seen that, although the benefits from the use of drugs for the human race beyond doubt, there are a lot of work to reduce their negative side-effects in the environment and living organisms. Chemists and engineers should keep in mind these ideas in the development and production of new drugs, like all of us who use drugs in our favour. This paper will describe the successful therapeutics – LDOPA - which is known as a remedy for alleviating the symptoms of Parkinson’s disease, and its advantages and potential dangers. Industrial production of L-DOPA will also be discussed, as well as its impact on the environment.